The Effects of Different Sources of Organic Manures in Growth and Yield of radish (Raphanus sativus L.) - Khatri, Keshar Bahadur; Ojha, Roshan Babu; Pande, Keshab Raj; Khanal, Babu Ram (International Journal of Applied Sciences and Biotechnology, 2019)
A field experiment was conducted in an Inceptisols with sandy loam soil of the research farm of Agriculture and Forestry University, Rampur, Chitwan, Nepal from October 2016 to January 2017 to evaluate the effects of different sources of organic manure in growth and yield of radish. The experiment was carried out in a Randomized Complete Block Design with six treatments (Poultry manure, goat manure, FYM, biogas byproduct, recommended dose of fertilizer and control) and was replicated four times. Pyuthane Red variety (released on 1994) of radish was used as a test crop. After analysis of primary nutrients of the organic manures, the amount was fixed on the basis of recommended nitrogen (100 kg N per hectare) as a reference value. The application of organic manures significantly increased the plant height, number of leaves, leaf breadth, root length, root diameter and biomass yield. The highest biomass yield (75.16 Mg/ha) and highest root yield (49.41 Mg/ha) was obtained from poultry manure application which was similar with recommended rate of fertilizer. The study suggested that application of poultry was found more beneficial and significantly improved growth and yield of radish. Int. J. Appl. Sci. Biotechnol. Vol 7(1): 39-42